ANALISIS KANDUNGAN BORAKS PADA KERUPUK NASI YANG DIJUAL DI PASAR TRADISIONAL KABUPATEN TANGGAMUS SECARA SPEKTROFOTOMETRI UV-Vis - Samsuar Samsuar; Akhmad Rokiban; Suparsi Suparsi (Fakultas MIPA Universitas Tulang Bawang Lampung, 2018)
The use of additional subtance for food is to increase or to maintain nutritional value and quality of storability. Our govermment prohibits the use of borax as an additives subtance for food as appointed in Permenkes No.033, 2012. Borax is a chemical compound in white colorless crystalline with a chemical formula Na2B4O7.10H2O. Rice crackers are crackers made from rice with spices and flavor enhancer. In manufacturing crackers Borax is sometimes added to get savory crackers and to make them swelling. The purpose of this study is to find out the borax content on rice crackers in traditional markets Tanggamus district by using the qualitative method. It uses the flame test, cucurmin reagen test and ammonia steam test. It also applies quantitative test by using spectophotometry UV-Vis. There are 8 samples which were taken in tradisional markets Tanggamus district. The result of determination of the maximum length waves is 543 nm. This method has been validated before being used for the samples. The resulf of the research shows a curve with linear calibration,with the regression equalition y = 0,539x + 0,009 and correlation coefficient (r) = 0,9979. The average recorvery or accuracy value is 104,71 %. The precision or the result of standartd deviation and standard deviation relative or coeffecient of variation (CV) is 0,219%. The LOD acquistion value is 0,069 µg/ml and the LOQ is 0,320 µg/ml. The validation of the test shows that all methods have been done are valid, so it can be used to test the borax assay on the samples. Based on the analysis on 8 samples of rice crackers, quanlitative obtained sample testing shows 6 detected containing borax, then the result of quantitative obtained the level of borax ranged from 46,75 µg/g until 107 µg/g. Keywords : borax, rice crackers, Spectrofometry UV-Vis